Education as An Important Dimension of the Poverty - Bici, Ruzhdie; Dr. Mirësi Çela (European Journal of Multidisciplinary Studies, 2017)
Poverty is an important phenomenon affecting individual and household life. It is important to know the factors that influence the possibility of being poor. An important cause and effect of poverty, one of the ones multidimensional nature of poverty is education level. Mostly, when we speak for the poverty, we based our estimates in the monetary terms, income or consumption. There are other dimensions like education, health, infrastructure, access in basic services, etc, that influence the economic and financial situation of the individuals. In Albania, to calculate the absolute poverty line is used the monetary poverty based on the consumption. The data refers to the Living Standard Measurement Survey (LSMS), which gives us the possibility to have multi indicators and also disaggregate and test the relationship and influence. The main objective of this paper is to analyze the influence of different indicators, mainly related with education and analyzing the influence on the poverty reduction. This research is based on Living Standard Measurement Survey (LSMS). This is a multidimensional survey collected near households and it collects information for living conditions, health, education, poverty, assets, migration etc. Is is used descriptive analyses and multinominal regression to analyse the trend on education and the significance on categories of different factors inluenced the education level. At the end we conclude that education is an influenced factors but also influence the poverty.
Keywords: Poverty, UBN, logistic regression, education.